Mixed response and mechanisms of resistance to larotrectinib in metastatic carcinoma ex pleomorphic adenoma of the parotid harboring an NTRK2 fusion: A case report. Issue 4 (29th January 2021) - Pircher, Magdalena; Briner, Hans Rudolf; Bonomo, Marco; Horcic, Milo; Petrausch, Ulf; Helbling, Daniel; Winder, Thomas
Abstract: Introduction: Standardized systemic treatment options are lacking for carcinoma ex pleomorphic adenoma, which is a rare and aggressive tumor primarily found in salivary glands. Here we report the case of a 63-year-old male with carcinoma ex pleomorphic adenoma of the left parotid and parapharyngeal space harboring a neurotrophic receptor tyrosine kinase ( NTRK) 2 fusion who was treated with a small molecule inhibitor that targets the tropomyosin receptor kinase (TRK) proteins. To the best of our knowledge, no similar case has been described in the literature so far. Patient concerns: After multiple surgical resections and radiotherapy for localized cancer disease over several years, our patient again developed an increasing swelling and pain around the left ear and numbness of the left half of the face. Diagnosis: Magnetic resonance imaging and positron emission tomography/computed tomography scans showed tumor recurrence in the left parotid, below the left ear, and in the parapharyngeal space, as well as metastases of the lungs and cervical lymph nodes. As data on the efficacy of systemic therapies for inoperable carcinoma ex pleomorphic adenoma are scarce, we performed a next-generation sequencing that revealed the presence of a hitherto unknown NTRK2 fusion. Interventions: Treatment with the TRK inhibitor larotrectinib was initiated, which induced rapid symptom improvement. However, part of the tumor had to be removed shortly afterwards due to local progression. Molecular testing did not demonstrate any alterations accounting for resistance to larotrectinib, with maintenance of the NTRK2 fusion. Outcomes: Three months later, imaging confirmed mixed response. While the reason for this remains unknown, the patient is in good condition and continues to receive larotrectinib. Conclusion: It remains unclear why our patient showed mixed response to larotrectinib and further studies are needed to explore other possible mechanisms of resistance. Abstract : Supplemental Digital Content is available in the text